Teaching portfolio as one of the leading ways of higher education teachers professional development in the USA - Belmaz, Yaroslava (My University, 2019)
The article deals with the issue of teaching portfolio. The author examines American educators’ understanding of essence “teaching portfolio”. It is mentioned that teaching portfolio is a certain stage of professional development of higher education teachers.Summing up, the author considers the teaching portfolio as a complex phenomenon that covers all of the above-mentioned aspects – a means for documenting the teaching process, reflecting patterns of teaching practice, emphasizing the main mission of the university, and most importantly – as motivation of the individual professional development of each faculty member. However, as noted by academic teachers, it is important to present not only an ideal experience, but also to describe problem situations, reflect on the way of their solution, on the causes of their occurrence, and others like that.
Belmaz Y. Teaching portfolio as one of the leading ways of higher education teachers professional development in the USA / Y. Belmaz // Наукові записки кафедри педагогіки : зб. наук. праць / редкол.: В.Г. Пасинок (голов. ред.) та ін. – Харків, 2018. – Вип. 42. – С. 19-24.
Keywords: викладач, вища школа, портфоліо, професійний розвиток, рефлексія, професійна діяльність; teacher, higher education, portfolio, professional development, reflection, professional activity; преподаватель, высшая школа, портфолио, профессиональное развитие, рефлексия, профессиональная деятельность